To purchase or not? Consumers’ organic food purchase intentions in Selangor during post COVID-19 pandemic / Nurul Huda Ismail ... [et al.] - Ismail, Nurul Huda; Tumin, Siti Aisyah; Abdul Kadir, Mohamad Arif; Abdul Latip, Muhammad Safuan; Mohamad, Mohamad Amiruddin (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This study investigates customers’ intentions to purchase organic food for the new normal life postCOVID-19 pandemic. The TPB has been employed as an underlying theory for the study. A purposive sampling approach was used, and 320 valid responses were collected from individuals residing in Selangor. Statistical Package for the Social Sciences (IBM SPSS) was applied in the data analysis for this study. The results illustrated that there is a significant relationship between consumer intention to purchase organic food with food safety knowledge, perceived attitude, perceived social pressure, and perceived autonomy. The research provided benefits to both organic food marketers and manufacturers by enhancing their understanding of the market and the sustainability of the organic food industry, particularly in the context of a new normal post-pandemic. The results could be used for benchmarking in future research on organic food because a new research framework was designed and validated regarding individual buying behaviour in global health issues, which is limited in current literature. As a result, the research provides a better understanding of consumers’ intention to purchase organic food.